Analisis Proses Pengambilan Keputusan Pemasaran Digital pada Pelaku UMKM di Papua - Jusmawati Jusmawati; Siti Nurhayati; Andrian Sah (Indo Green Journal, 2026)
This study aims to analyze the digital marketing decision-making process of MSME actors in Papua and identify factors influencing their marketing strategies. A qualitative case study approach was employed, combining semi-structured interviews, participatory observation, and documentation of digital marketing materials. Findings indicate that digital marketing decisions are affected by internal factors such as digital literacy, data analysis capabilities, content creativity, and management capacity, as well as external factors including infrastructure, internet access, consumer characteristics, and logistics. MSMEs that align their digital strategies with internal capacities and external challenges demonstrate higher marketing effectiveness, including improved product visibility, consumer engagement, and sales. Adaptive strategies applied, such as collaboration with local influencers, daily promotion packages, educational content, flash sales, and posting frequency adjustments, reflect the MSMEs’ ability to overcome resource limitations. This study expands the literature on digital marketing and information systems by presenting a contextualized decision-making model for MSMEs in remote areas while providing practical implications for MSME actors, policymakers, and supporting institutions.